2009
DOI: 10.1177/0883073808322673
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Congenital Anomalies/Mental Retardation Syndrome With Multiple Circumferential Skin Creases: A New Syndrome?

Abstract: We describe a combination of multiple congenital anomalies, a severe psychomotor retardation and seizures in a 9-year-old Tunisian boy with circumferential ringed skin creases. He had symmetrical circumferential skin creases on arms, legs, and penis. Craniofacial anomalies included: an elongated face, tight forehead, hypertelorism, bilateral epicanthic folds, upslanting palpebral fissures, microphthalmia, convergent strabismus, wide nasal bridge, aberrant teeth, dental caries, and low-set posteriorly rotated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The pathophysiology of these skin creases is not clear. It may result from a variety of underlying abnormalities including nevus lipomatosus, smooth muscle hamartoma, fragmented elastic fibers with smooth muscle hamartoma or the skin may be normal histopathologically [25]. …”
Section: Syndromesmentioning
confidence: 99%
“…The pathophysiology of these skin creases is not clear. It may result from a variety of underlying abnormalities including nevus lipomatosus, smooth muscle hamartoma, fragmented elastic fibers with smooth muscle hamartoma or the skin may be normal histopathologically [25]. …”
Section: Syndromesmentioning
confidence: 99%
“…Tinsa et al in 2009 and Basel‐Vanagaite et al in 2011 also attempted to label other patients as having folded skin syndromes distinct from MTBS, each group describing one patient with circumferential skin folds along with multiple other anomalies. In 2011, Wouters et al reported two unrelated patients with folds and other anomalies and coined the name “circumferential skin creases Kunze type” to describe their patient and six that Kunze had described in 1982.…”
Section: Historymentioning
confidence: 99%
“…In most cases with the MTB phenotype in which biopsy has been performed, pathologic examination has shown underlying smooth muscle hamartoma or nevus lipomatosus . Other cases have revealed degenerative collagen or scarring on pathology, and in a number of cases, biopsies showed normal skin or were not performed .…”
mentioning
confidence: 99%
“…Congenital symmetrical circumferential skin creases (CSC; OMIM 156610, 616734) is a rare disease characterized by folding of excess skin, which leads to generalized ringed creases, primarily of the limbs, generally with spontaneous improvement. 1,2 This peculiar disorder was first described in 1969 and was originally named as "Michelin Tire Baby Syndrome" (MTBS), 3 because of the similarity with the cartoon mascot of the French company. Additional CSC patients have been reported with facial dysmorphism, intellectual disability (ID) and multiple congenital anomalies (MCA).…”
Section: Introductionmentioning
confidence: 99%
“…Additional CSC patients have been reported with facial dysmorphism, intellectual disability (ID) and multiple congenital anomalies (MCA). 1,2,[4][5][6][7][8][9][10] Wouters et al coined the term "CSC Kunze Type" (CSC-KT) for patients who presented, in addition to CSC, a pattern of malformations with cleft palate, facial dysmorphism, growth retardation, genital abnormalities and ID. 2,4 Isrie et al 11 reported mutations in either MAPRE2 or TUBB genes, in 4 and 3 CSC-KT patients, respectively.…”
Section: Introductionmentioning
confidence: 99%